1993
DOI: 10.1159/000247351
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Partially Symmetric Erythrokeratodermia with Deafness: Histological and Ultrastructural Evidence for a Subtype Distinct from Schnyder’s Syndrome

Abstract: An atypical case of the rare genodermatosis erythrokeratodermia progressiva partim symmetrica (EPPS) with deafness and myopathy is described. Our findings suggest that this case of EPPS with deafness and myopathy represents a distinct entity of atypical erythrokeratodermias with characteristic epidermal and dermal skin changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…[7][8][9] Several authors accept the existence of a nonmigratory but progressive erythrokeratoderma, called progressive symmetric erythrokeratoderma (PSEK) or Gottron erythrokeratoderma. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] However, it has been demonstrated that within sibships, erythrokeratodermas can be static or migratory and can even pass from one state to another, indicating that their distinction may not be valid. 24 Furthermore, the nosology has been muddled by confusion about what 'keratoderma' means, with the term used both for the peculiar starfish lesions of Vohwinkel's syndrome and loricrin keratoderma as well as the scaling hyperkeratosis of erythrokeratoderma variabilis.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Several authors accept the existence of a nonmigratory but progressive erythrokeratoderma, called progressive symmetric erythrokeratoderma (PSEK) or Gottron erythrokeratoderma. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] However, it has been demonstrated that within sibships, erythrokeratodermas can be static or migratory and can even pass from one state to another, indicating that their distinction may not be valid. 24 Furthermore, the nosology has been muddled by confusion about what 'keratoderma' means, with the term used both for the peculiar starfish lesions of Vohwinkel's syndrome and loricrin keratoderma as well as the scaling hyperkeratosis of erythrokeratoderma variabilis.…”
Section: Discussionmentioning
confidence: 99%
“…Later other cases with keratitis and recurrent skin Infections as additional features were re-Corresponding author. ported [4][5][6][7][8][9]. The following case report has many similarities with the atypical erythrokeratodermia first reported by Burns [2] and later by Schnyder et al [3].…”
Section: Introductionmentioning
confidence: 60%
“…In 1981 Skinner et al [10] defined a condition they called KID syndrome (keratitis ichthyosis deafness). This entity was later disputed by Lamprect et al in 1988 [7] and Kiesewetter et al, [8] in 1993. and we agree that patients who present symmetric erthematous hyperkeratotic plaques, deafness and missing ichthyosis should be diagnosed as progressive erythrokeratodermia with deafness. Teeth anomalies including dental dysplasia have been described as additional factors in some patients [9.12].…”
Section: Discussionmentioning
confidence: 99%
“…Nesses pacientes, a análise da pele à microscopia eletrônica difere dos demais, por apresentar alterações no nível da junção dermoepidérmi-ca, o que sugere uma variante atípica da EQSP. 8 O principal diagnóstico diferencial a ser lembrado é a EQV, descrita por Mendes da Costa em 1925. Nessa entidade, ocorrem áreas de eritema com expansão centrífuga, que podem variar rápida ou lentamente, associadas a placas ceratósicas persistentes; as lesões podem ser induzidas por alterações na temperatura ambiental, estresse emocional e pressão mecânica.…”
Section: Discussionunclassified